A PVC auxiliary agent composition based on thermal stability and a preparation method thereof

CN122958809APending Publication Date: 2026-10-23TAIYUAN UNIVERSITY OF TECHNOLOGY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611460655.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-20
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0003]本发明的目的在于提供一种基于热稳定性的PVC助剂组合物及其制备方法,以解决上述背景技术提出的传统PVC热稳定剂含重金属铅的技术问题

Benefits of technology

氯化聚氯乙烯凭借高氯含量与PVC的相容性,提升体系热分解阈值;改性水滑石通过层状结构物理吸附HCl,硬脂酸钙与硬脂酸锌形成“钙锌协同”中和HCl,切断脱HCl自催化循环;环氧大豆油降低分子链摩擦减少热应力降解,酚类抗氧化剂捕获氧化自由基,多重机制共同作用下,大幅提高PVC的热稳定性能;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a PVC additive composition based on thermal stability and a preparation method thereof, and relates to the technical field of polymer additive materials.The preparation method comprises the following steps: adding chlorinated polyvinyl chloride, modified hydrotalcite, calcium stearate, zinc stearate, epoxy soybean oil and a phenolic antioxidant into a high-speed mixer, uniformly stirring and mixing, obtaining mixed materials, adding the mixed materials into a double-screw extruder, performing extrusion granulation, and obtaining the PVC additive composition.The thermal stabilizer does not contain heavy metal substances which are harmful to the environment and human bodies, and is green and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer additive materials technology, specifically to a method for preparing a PVC additive composition based on thermal stability. Background Technology

[0002] Polyvinyl chloride (PVC), one of the world's five major plastics, boasts advantages such as low price and wide application, finding extensive use in agriculture, industry, transportation, and many other fields. However, PVC has a significant drawback: it exhibits sensitivity and poor stability under the influence of light, heat, oxygen, and external forces. During thermoplastic processing, PVC is highly susceptible to degradation at high temperatures if left untreated. To prevent this degradation, heat stabilizers are typically added during PVC processing to inhibit it. Currently, common PVC heat stabilizers on the market mainly include lead salts, metal soaps, and organotin compounds, which account for over 90% of the PVC heat stabilizer market share. Among these, lead salt heat stabilizers were widely used in the past due to their low price, excellent thermal stability, and good weather resistance; for example, they were a common choice in PVC wire and cable processing. However, lead salt heat stabilizers have a serious drawback: lead is a heavy metal with significant toxicity. In the production process, such as in the wire and cable industry, most manufacturers use rudimentary equipment, resulting in a pervasive presence of lead dust on the production line. Even with simple protective measures, workers often cannot effectively prevent lead dust from entering their bodies. Prolonged exposure to lead dust can lead to a continuous increase in lead levels in the lungs and respiratory system, eventually causing lead poisoning. Furthermore, the unorganized emission of lead dust not only covers the floors and equipment of production workshops with lead-containing raw material dust but also causes heavy metal pollution in the surrounding environment due to rainwater runoff and wind propagation. In the usage stage, when lead-containing PVC plastic water pipes are in use, lead can leach from the pipes, directly contaminating drinking water. Currently, lead-containing plastic water pipes are banned in many countries worldwide, and Beijing and Shanghai in my country have also passed decisions banning lead in water pipes. In addition, the Ministry of Electric Power stipulates that, to prevent environmental pollution, the use of lead salts and organotin stabilizers is prohibited for CPVC power protection pipes within the scope of the Ministry's grid access permit. With the increasing global awareness of environmental protection and health, the threat posed by traditional lead-containing PVC heat stabilizers to resources, environment and human health has attracted increasing attention. Developed countries, represented by Europe, have long since restricted or even banned the use of lead salt PVC plastic product stabilizers on a large scale. Summary of the Invention

[0003] The purpose of this invention is to provide a PVC additive composition based on thermal stability and its preparation method, thereby solving the technical problem mentioned in the background section regarding the presence of heavy metal lead in traditional PVC heat stabilizers. The heat stabilizer of this invention does not contain any heavy metals that pollute the environment or are harmful to human health, making it green and environmentally friendly.

[0004] To achieve the above objectives, the present invention provides the following technical solution: A PVC additive composition based on thermal stability, comprising the following components in parts by weight: 30-40 parts of chlorinated polyvinyl chloride, 20-30 parts of modified hydrotalcite, 5-10 parts of calcium stearate, 3-5 parts of zinc stearate, 3-5 parts of epoxidized soybean oil, and 1-3 parts of phenolic antioxidants.

[0005] At temperatures above 100°C, the C-Cl bonds in polyvinyl chloride (PVC) easily break, releasing HCl. This released HCl acts as a protic acid, catalyzing the deHCl removal from adjacent molecular chains, forming an "autocatalytic cycle." Simultaneously, oxygen and other substances accelerate this process, leading to the formation of conjugated double bonds in the PVC molecular chains, resulting in yellowing and degradation. In this invention, chlorinated PVC is used as a heat-stabilizing additive resin. Chlorinated PVC, due to its high chlorine content and good compatibility with PVC, has a higher thermal decomposition temperature than PVC, thus increasing the system's thermal decomposition threshold. The layered structure of modified hydrotalcite can physically adsorb HCl, reducing the amount of HCl released from the material and preventing the autocatalytic cycle of PVC upon heating. Calcium stearate and zinc stearate form a "calcium-zinc synergy," which can neutralize the generated HCl. Epoxidized soybean oil can reduce friction between PVC molecular chains, minimizing degradation caused by processing thermal stress. Phenolic antioxidants provide active hydrogen to capture oxidative free radicals, preventing the oxidative breakage of PVC molecular chains. Through the synergistic effect of these components, the thermal stability of PVC is improved.

[0006] Preferably, the method for preparing the modified hydrotalcite includes the following steps: S1. Add magnesium nitrate and aluminum nitrate to deionized water, stir to dissolve, and obtain a metal ion solution; S2. Add polyvinylpyrrolidone to deionized water, stir to dissolve, then add polystyrene microspheres, heat and stir to disperse evenly, to obtain a polystyrene microsphere suspension; S3. Add sodium hydroxide and sodium carbonate to deionized water, stir to dissolve, and obtain a mixed alkaline solution; S4. Add the polystyrene microsphere suspension to the metal ion solution, heat and stir until uniform, then slowly add the mixed alkaline solution to adjust the pH to 9-10, heat and stir to react, so that hydrotalcite is deposited and grown on the surface of polystyrene microspheres, and perform hydrothermal aging treatment. After filtration, washing and drying, polystyrene microsphere-hydrotalcite composite is obtained. S5. The polystyrene microsphere-hydrotalcite composite was calcined in a muffle furnace to obtain porous hydrotalcite. S6. Porous hydrotalcite is modified by stearic acid intercalation to obtain modified hydrotalcite.

[0007] In this invention, modified hydrotalcite adsorbs HCl from PVC molecules by breaking the C-Cl bonds. Calcium stearate and zinc stearate form a "calcium-zinc synergistic" reaction, and the HCl produced is then synergistically removed through the interaction of these two substances. The principle of modified hydrotalcite preparation is as follows: First, a co-precipitation reaction is induced on the surface of polystyrene microspheres using a magnesium nitrate and aluminum nitrate metal ion solution, a polyvinylpyrrolidone-dispersed polystyrene microsphere suspension, and a sodium hydroxide-sodium carbonate mixed alkaline solution. After hydrothermal aging, a "microsphere-hydrotalcite" composite precursor is formed. Then, the polystyrene template is removed by calcination in a muffle furnace, utilizing the space occupied by the template agent to form a porous structure, achieving better adsorption of hydrogen chloride. Mg in the hydrotalcite layers... 2+ Al 3+ By coordinating with HCl molecules, the mesoporous structure provides physical adsorption sites, increasing the contact area with HCl. Furthermore, the porous structure formed by calcination shortens the diffusion path of HCl, resulting in a significant increase in the adsorption capacity of porous hydrotalcite for HCl compared to ordinary hydrotalcite.

[0008] Furthermore, this invention removes HCl by synergistically combining the adsorption of hydrogen chloride by hydrotalcite with the neutralization of HCl by calcium stearate and zinc stearate. To enhance the synergistic effect, this invention further modifies the porous hydrotalcite by intercalating it with stearic acid. The residual carboxyl groups on the surface can form "carboxyl-metal ion" coordination bonds with calcium stearate / zinc stearate, thereby allowing calcium stearate and zinc stearate to combine with the hydrotalcite. The hydrogen chloride adsorbed by the hydrotalcite can be efficiently neutralized and removed. Compared with the hydrotalcite without intercalation modification, the HCl removal rate is significantly improved, thereby further enhancing the thermal stability of PVC materials.

[0009] Preferably, in step S4, the amount of polystyrene microspheres added is 2-5% of the total mass of magnesium nitrate and aluminum nitrate.

[0010] Preferably, in step S4, the reaction temperature for heating and stirring is 50-60°C.

[0011] Preferably, in step S4, the hydrothermal aging treatment temperature is 100-120℃.

[0012] Preferably, in step S5, the calcination temperature is 300-400℃.

[0013] Preferably, in step S6, the stearic acid intercalation modification treatment method includes the following steps: Porous hydrotalcite is added to an ethanol solution of stearic acid, heated and stirred to react, and then filtered, washed and dried to obtain the final product.

[0014] Preferably, the mass ratio of the porous hydrotalcite to stearic acid is 10:2-4.

[0015] In the technical solution of this invention, as mentioned above, to better achieve the adsorption and neutralization removal of hydrogen chloride, the porous layered double hydroxide (LDH) is modified by stearic acid intercalation, allowing calcium stearate and zinc stearate to combine with the LDH, thereby increasing the neutralization and removal capacity of hydrogen chloride by calcium stearate and zinc stearate. To better achieve the combination of calcium stearate and zinc stearate with the LDH, the porous LDH must be combined with a sufficient amount of stearic acid. Therefore, this invention controls the mass ratio of porous LDH to stearic acid to be less than 10 / 2. With the increase of stearic acid content, the invention team unexpectedly discovered that when the mass ratio of porous LDH to stearic acid is less than 10 / 4, the adsorption capacity of the LDH for hydrogen chloride suddenly and significantly decreases. Research revealed that this is because, with excessive intercalation, stearic acid molecules form "cluster-like accumulations" within the pores, changing the pore size distribution from a single peak to a broad peak, reducing the average pore size to below 2 nm, and even causing pore blockage, thus reducing the adsorption capacity of the LDH for hydrogen chloride. Therefore, this invention strictly controls the mass ratio of porous hydrotalcite to stearic acid within the required range, thereby avoiding the pore blockage of porous hydrotalcite caused by stearic acid and significantly improving the bonding force between hydrotalcite and calcium stearate and zinc stearate.

[0016] Preferably, the reaction temperature of the heating and stirring reaction in the stearic acid intercalation modification method is 80-85℃.

[0017] A method for preparing a PVC additive composition based on thermal stability includes the following steps: Chlorinated polyvinyl chloride, modified hydrotalcite, calcium stearate, zinc stearate, epoxidized soybean oil, and phenolic antioxidants are added to a high-speed mixer and stirred until homogeneous to obtain a mixture. The mixture is added to a twin-screw extruder and extruded and granulated to obtain a PVC additive composition.

[0018] Compared with the prior art, the beneficial effects of the present invention are: Chlorinated polyvinyl chloride (PVC) improves the thermal decomposition threshold of the system due to its high chlorine content and compatibility with PVC. Modified hydrotalcite physically adsorbs HCl through its layered structure, and calcium stearate and zinc stearate form a "calcium-zinc synergy" to neutralize HCl, thus cutting off the autocatalytic cycle of HCl removal. Epoxidized soybean oil reduces molecular chain friction and thermal stress degradation, while phenolic antioxidants capture oxidative free radicals. Under the combined action of multiple mechanisms, the thermal stability of PVC is significantly improved. After stearic acid intercalation, the interlayer spacing of porous hydrotalcite increases, and the surface carboxyl groups form coordination bonds with calcium / zinc stearate, enabling the efficient neutralization of HCl adsorbed by the hydrotalcite by calcium / zinc stearate. This "adsorption-neutralization" mechanism significantly improves the HCl removal rate compared to single adsorption or neutralization methods.

[0019] This invention strictly controls the mass ratio of porous hydrotalcite to stearic acid within the required range, thereby avoiding the pore blockage of porous hydrotalcite caused by stearic acid and significantly improving the bonding force between hydrotalcite and calcium stearate and zinc stearate. Detailed Implementation

[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0021] Example 1

[0022] A PVC additive composition based on thermal stability, comprising the following components in parts by weight: 38 parts of chlorinated polyvinyl chloride, 27 parts of modified hydrotalcite, 9 parts of calcium stearate, 4 parts of zinc stearate, 4 parts of epoxidized soybean oil, and 2 parts of phenolic antioxidant (1010).

[0023] Preparation of modified hydrotalcite: Step S1: Weigh 29.2g magnesium nitrate and 16.8g aluminum nitrate, add them to 200mL of deionized water, place them on a magnetic stirrer, and stir at room temperature for 30 minutes until completely dissolved to obtain a clear and transparent metal ion solution; Step S2: Add 2.0g of polyvinylpyrrolidone to 100mL of deionized water and stir to dissolve in a 50℃ water bath. Then add 2.0g of polystyrene microspheres (particle size 200nm), transfer to a three-necked flask, and stir in a 60℃ oil bath at 200r / min for 1 hour to uniformly disperse the polystyrene microspheres and obtain a polystyrene microsphere suspension. Step S3: Take 8.0g of sodium hydroxide and 4.2g of sodium carbonate, add them to 200mL of deionized water, stir until dissolved, filter through a 0.45μm filter membrane to obtain a mixed alkaline solution for later use.

[0024] Step S4: The prepared polystyrene microsphere suspension was added to a metal ion solution and stirred in an oil bath at 55°C for 30 minutes. Then, a mixed alkaline solution was slowly added dropwise at a rate of 5 mL / min to adjust the pH to 9.5. After the addition was complete, the reaction mixture was stirred for another 4 hours. The reaction solution was transferred to a 500 mL hydrothermal reactor and aged at 110°C for 24 hours. After cooling, the mixture was washed three times each with deionized water and ethanol, and then vacuum dried at 80°C for 12 hours to obtain a white powdery polystyrene microsphere-hydrotalcite composite.

[0025] Step S5: Place the polystyrene microsphere-hydrotalcite composite in a crucible, put it in a muffle furnace, heat it to 350°C at a heating rate of 5°C / min, calcine it at a constant temperature for 3 hours, and grind it through a 200-mesh sieve after natural cooling to obtain porous hydrotalcite with a mesoporous structure.

[0026] Step S6: Weigh 10g of porous hydrotalcite and 3.5g of stearic acid. Dissolve the stearic acid in 50mL of ethanol. Add the porous hydrotalcite and transfer it to a three-necked flask. Reflux and stir in an oil bath at 83℃ for 4 hours. After the reaction is complete, filter the mixture, wash it twice with ethanol, and dry it under vacuum at 60℃ for 8 hours to obtain the modified hydrotalcite.

[0027] A method for preparing a PVC additive composition based on thermal stability includes the following steps: Chlorinated polyvinyl chloride, modified hydrotalcite, calcium stearate, zinc stearate, epoxidized soybean oil and phenolic antioxidants were added to a high-speed mixer and stirred at 800 r / min at room temperature for 10 minutes until the components were evenly dispersed and there was no obvious agglomeration, thus obtaining a mixture. The premixed material is added to a twin-screw extruder. The extruder temperatures are set as follows: feeding section 160℃, melting section 180℃, homogenizing section 190℃, and die head 200℃. The screw speed is controlled at 150 r / min, and the feeding rate is 10 kg / h. After melt blending and extrusion, the material is water-cooled and pelletized to collect particles with a diameter of 2-3 mm. These particles are then vacuum-dried at 50℃ for 4 hours to obtain the final product.

[0028] Example 2

[0029] A PVC additive composition based on thermal stability, comprising the following components in parts by weight: 32 parts of chlorinated polyvinyl chloride, 21 parts of modified hydrotalcite, 6 parts of calcium stearate, 4 parts of zinc stearate, 4 parts of epoxidized soybean oil, and 2 parts of phenolic antioxidant (1010).

[0030] Preparation of modified hydrotalcite: Step S1: Weigh 29.2g magnesium nitrate and 16.8g aluminum nitrate, add them to 200mL of deionized water, place them on a magnetic stirrer, and stir at room temperature for 30 minutes until completely dissolved to obtain a clear and transparent metal ion solution; Step S2: Add 2.0g of polyvinylpyrrolidone to 100mL of deionized water and stir to dissolve in a 50℃ water bath. Then add 1.0g of polystyrene microspheres (particle size 200nm), transfer to a three-necked flask, and stir in a 60℃ oil bath at 200r / min for 1 hour to uniformly disperse the polystyrene microspheres and obtain a polystyrene microsphere suspension. Step S3: Take 8.0g of sodium hydroxide and 4.2g of sodium carbonate, add them to 200mL of deionized water, stir until dissolved, filter through a 0.45μm filter membrane to obtain a mixed alkaline solution for later use.

[0031] Step S4: The prepared polystyrene microsphere suspension was added to a metal ion solution and stirred in an oil bath at 55°C for 30 minutes. Then, a mixed alkaline solution was slowly added dropwise at a rate of 5 mL / min to adjust the pH to 9.5. After the addition was complete, the reaction mixture was stirred for another 4 hours. The reaction solution was transferred to a 500 mL hydrothermal reactor and aged at 110°C for 24 hours. After cooling, the mixture was washed three times each with deionized water and ethanol, and then vacuum dried at 80°C for 12 hours to obtain a white powdery polystyrene microsphere-hydrotalcite composite.

[0032] Step S5: Place the polystyrene microsphere-hydrotalcite composite in a crucible, put it in a muffle furnace, heat it to 350°C at a heating rate of 5°C / min, calcine it at a constant temperature for 3 hours, and grind it through a 200-mesh sieve after natural cooling to obtain porous hydrotalcite with a mesoporous structure.

[0033] Step S6: Weigh 10g of porous hydrotalcite and 3g of stearic acid. Dissolve the stearic acid in 50mL of ethanol, add the porous hydrotalcite, and transfer to a three-necked flask. Reflux and stir in an oil bath at 83℃ for 4 hours. After the reaction is complete, filter, wash twice with ethanol, and dry under vacuum at 60℃ for 8 hours to obtain modified hydrotalcite.

[0034] A method for preparing a PVC additive composition based on thermal stability includes the following steps: Chlorinated polyvinyl chloride, modified hydrotalcite, calcium stearate, zinc stearate, epoxidized soybean oil and phenolic antioxidants were added to a high-speed mixer and stirred at 800 r / min at room temperature for 10 minutes until the components were evenly dispersed and there was no obvious agglomeration, thus obtaining a mixture. The premixed material is added to a twin-screw extruder. The extruder temperatures are set as follows: feeding section 160℃, melting section 180℃, homogenizing section 190℃, and die head 200℃. The screw speed is controlled at 150 r / min, and the feeding rate is 10 kg / h. After melt blending and extrusion, the material is water-cooled and pelletized to collect particles with a diameter of 2-3 mm. These particles are then vacuum-dried at 50℃ for 4 hours to obtain the final product.

[0035] Example 3

[0036] A PVC additive composition based on thermal stability, comprising the following components in parts by weight: 35 parts of chlorinated polyvinyl chloride, 25 parts of modified hydrotalcite, 7 parts of calcium stearate, 4 parts of zinc stearate, 4 parts of epoxidized soybean oil, and 2 parts of phenolic antioxidant (1010).

[0037] Preparation of modified hydrotalcite: Step S1: Weigh 29.2g magnesium nitrate and 16.8g aluminum nitrate, add them to 200mL of deionized water, place them on a magnetic stirrer, and stir at room temperature for 30 minutes until completely dissolved to obtain a clear and transparent metal ion solution; Step S2: Add 2.0g of polyvinylpyrrolidone to 100mL of deionized water and stir to dissolve in a 50℃ water bath. Then add 1.5g of polystyrene microspheres (particle size 200nm), transfer to a three-necked flask, and stir in a 60℃ oil bath at 200r / min for 1 hour to uniformly disperse the polystyrene microspheres and obtain a polystyrene microsphere suspension. Step S3: Take 8.0g of sodium hydroxide and 4.2g of sodium carbonate, add them to 200mL of deionized water, stir until dissolved, filter through a 0.45μm filter membrane to obtain a mixed alkaline solution for later use.

[0038] Step S4: The prepared polystyrene microsphere suspension was added to a metal ion solution and stirred in an oil bath at 55°C for 30 minutes. Then, a mixed alkaline solution was slowly added dropwise at a rate of 5 mL / min to adjust the pH to 9.5. After the addition was complete, the reaction mixture was stirred for another 4 hours. The reaction solution was transferred to a 500 mL hydrothermal reactor and aged at 110°C for 24 hours. After cooling, the mixture was washed three times each with deionized water and ethanol, and then vacuum dried at 80°C for 12 hours to obtain a white powdery polystyrene microsphere-hydrotalcite composite.

[0039] Step S5: Place the polystyrene microsphere-hydrotalcite composite in a crucible, put it in a muffle furnace, heat it to 350°C at a heating rate of 5°C / min, calcine it at a constant temperature for 3 hours, and grind it through a 200-mesh sieve after natural cooling to obtain porous hydrotalcite with a mesoporous structure.

[0040] Step S6: Weigh 10g of porous hydrotalcite and 3g of stearic acid. Dissolve the stearic acid in 50mL of ethanol, add the porous hydrotalcite, and transfer to a three-necked flask. Reflux and stir in an oil bath at 83℃ for 4 hours. After the reaction is complete, filter, wash twice with ethanol, and dry under vacuum at 60℃ for 8 hours to obtain modified hydrotalcite.

[0041] A method for preparing a PVC additive composition based on thermal stability includes the following steps: Chlorinated polyvinyl chloride, modified hydrotalcite, calcium stearate, zinc stearate, epoxidized soybean oil and phenolic antioxidants were added to a high-speed mixer and stirred at 800 r / min at room temperature for 10 minutes until the components were evenly dispersed and there was no obvious agglomeration, thus obtaining a mixture. The premixed material is added to a twin-screw extruder. The extruder temperatures are set as follows: feeding section 160℃, melting section 180℃, homogenizing section 190℃, and die head 200℃. The screw speed is controlled at 150 r / min, and the feeding rate is 10 kg / h. After melt blending and extrusion, the material is water-cooled and pelletized to collect particles with a diameter of 2-3 mm. These particles are then vacuum-dried at 50℃ for 4 hours to obtain the final product.

[0042] Example 4

[0043] A PVC additive composition based on thermal stability, comprising the following components in parts by weight: 40 parts of chlorinated polyvinyl chloride, 30 parts of modified hydrotalcite, 10 parts of calcium stearate, 5 parts of zinc stearate, 5 parts of epoxidized soybean oil, and 3 parts of phenolic antioxidant (1010).

[0044] Preparation of modified hydrotalcite: Step S1: Weigh 29.2g magnesium nitrate and 16.8g aluminum nitrate, add them to 200mL of deionized water, place them on a magnetic stirrer, and stir at room temperature for 30 minutes until completely dissolved to obtain a clear and transparent metal ion solution; Step S2: Add 2.0g of polyvinylpyrrolidone to 100mL of deionized water and stir to dissolve in a 50℃ water bath. Then add 2.3g of polystyrene microspheres (particle size 200nm), transfer to a three-necked flask, and stir in a 60℃ oil bath at 200r / min for 1 hour to uniformly disperse the polystyrene microspheres and obtain a polystyrene microsphere suspension. Step S3: Take 8.0g of sodium hydroxide and 4.2g of sodium carbonate, add them to 200mL of deionized water, stir until dissolved, filter through a 0.45μm filter membrane to obtain a mixed alkaline solution for later use.

[0045] Step S4: The prepared polystyrene microsphere suspension was added to a metal ion solution and stirred in an oil bath at 60°C for 30 minutes. Then, a mixed alkaline solution was slowly added dropwise at a rate of 5 mL / min to adjust the pH to 10. After the addition was complete, the reaction mixture was stirred for another 4 hours. The reaction solution was transferred to a 500 mL hydrothermal reactor and aged at 120°C for 24 hours. After cooling, the mixture was washed three times each with deionized water and ethanol, and then vacuum dried at 80°C for 12 hours to obtain a white powdery polystyrene microsphere-hydrotalcite composite.

[0046] Step S5: Place the polystyrene microsphere-hydrotalcite composite in a crucible, put it in a muffle furnace, heat it to 400℃ at a heating rate of 5℃ / min, calcine it at a constant temperature for 3 hours, and grind it through a 200-mesh sieve after natural cooling to obtain porous hydrotalcite with a mesoporous structure.

[0047] Step S6: Weigh 10g of porous hydrotalcite and 4g of stearic acid. Dissolve the stearic acid in 50mL of ethanol, add the porous hydrotalcite, and transfer to a three-necked flask. Reflux and stir in an oil bath at 85℃ for 4 hours. After the reaction is complete, filter, wash twice with ethanol, and dry under vacuum at 60℃ for 8 hours to obtain modified hydrotalcite.

[0048] A method for preparing a PVC additive composition based on thermal stability includes the following steps: Chlorinated polyvinyl chloride, modified hydrotalcite, calcium stearate, zinc stearate, epoxidized soybean oil and phenolic antioxidants were added to a high-speed mixer and stirred at 800 r / min at room temperature for 10 minutes until the components were evenly dispersed and there was no obvious agglomeration, thus obtaining a mixture. The premixed material is added to a twin-screw extruder. The extruder temperatures are set as follows: feeding section 160℃, melting section 180℃, homogenizing section 190℃, and die head 200℃. The screw speed is controlled at 150 r / min, and the feeding rate is 10 kg / h. After melt blending and extrusion, the material is water-cooled and pelletized to collect particles with a diameter of 2-3 mm. These particles are then vacuum-dried at 50℃ for 4 hours to obtain the final product.

[0049] Example 5

[0050] A PVC additive composition based on thermal stability, comprising the following components in parts by weight: 30 parts of chlorinated polyvinyl chloride, 20 parts of modified hydrotalcite, 5 parts of calcium stearate, 3 parts of zinc stearate, 3 parts of epoxidized soybean oil, and 1 part of phenolic antioxidant (1010).

[0051] Preparation of modified hydrotalcite: Step S1: Weigh 29.2g magnesium nitrate and 16.8g aluminum nitrate, add them to 200mL of deionized water, place them on a magnetic stirrer, and stir at room temperature for 30 minutes until completely dissolved to obtain a clear and transparent metal ion solution; Step S2: Add 2.0g of polyvinylpyrrolidone to 100mL of deionized water and stir to dissolve in a 50℃ water bath. Then add 0.92g of polystyrene microspheres (particle size 200nm), transfer to a three-necked flask, and stir in a 60℃ oil bath at 200r / min for 1 hour to uniformly disperse the polystyrene microspheres and obtain a polystyrene microsphere suspension. Step S3: Take 8.0g of sodium hydroxide and 4.2g of sodium carbonate, add them to 200mL of deionized water, stir until dissolved, filter through a 0.45μm filter membrane to obtain a mixed alkaline solution for later use.

[0052] Step S4: The prepared polystyrene microsphere suspension was added to a metal ion solution and stirred in an oil bath at 50°C for 30 minutes. Then, a mixed alkaline solution was slowly added dropwise at a rate of 5 mL / min to adjust the pH to 9. After the addition was complete, the reaction mixture was stirred for another 4 hours. The reaction solution was transferred to a 500 mL hydrothermal reactor and aged at 100°C for 24 hours. After cooling, the mixture was washed three times each with deionized water and ethanol, and then vacuum dried at 80°C for 12 hours to obtain a white powdery polystyrene microsphere-hydrotalcite composite.

[0053] Step S5: Place the polystyrene microsphere-hydrotalcite composite in a crucible, put it in a muffle furnace, heat it to 300°C at a heating rate of 5°C / min, calcine it at a constant temperature for 3 hours, and grind it through a 200-mesh sieve after natural cooling to obtain porous hydrotalcite with a mesoporous structure.

[0054] Step S6: Weigh 10g of porous hydrotalcite and 2g of stearic acid. Dissolve the stearic acid in 50mL of ethanol, add the porous hydrotalcite, and transfer to a three-necked flask. Reflux and stir in an oil bath at 80℃ for 4 hours. After the reaction is complete, filter, wash twice with ethanol, and dry under vacuum at 60℃ for 8 hours to obtain modified hydrotalcite.

[0055] A method for preparing a PVC additive composition based on thermal stability includes the following steps: Chlorinated polyvinyl chloride, modified hydrotalcite, calcium stearate, zinc stearate, epoxidized soybean oil and phenolic antioxidants were added to a high-speed mixer and stirred at 800 r / min at room temperature for 10 minutes until the components were evenly dispersed and there was no obvious agglomeration, thus obtaining a mixture. The premixed material is added to a twin-screw extruder. The extruder temperatures are set as follows: feeding section 160℃, melting section 180℃, homogenizing section 190℃, and die head 200℃. The screw speed is controlled at 150 r / min, and the feeding rate is 10 kg / h. After melt blending and extrusion, the material is water-cooled and pelletized to collect particles with a diameter of 2-3 mm. These particles are then vacuum-dried at 50℃ for 4 hours to obtain the final product.

[0056] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the PVC additive composition does not contain modified hydrotalcite, otherwise they are the same.

[0057] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the PVC additive composition does not contain calcium stearate and zinc stearate, but the rest are the same.

[0058] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the modified hydrotalcite is replaced with ordinary hydrotalcite in the PVC additive composition.

[0059] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the porous hydrotalcite is not subjected to stearic acid intercalation treatment during the preparation of the modified hydrotalcite; that is, the modified hydrotalcite is replaced with porous hydrotalcite. The other steps are the same.

[0060] Comparative Example 5 The difference between Comparative Example 5 and Example 4 is that the mass ratio of porous hydrotalcite to stearic acid in the preparation of modified hydrotalcite is 10:5, while the other steps are the same.

[0061] Comparison Example The control example is a composition without PVC additives, pure PVC resin.

[0062] Performance testing: 1. Thermal stability test: PVC resin and PVC additives (mass ratio 100:1) were mixed evenly. Then, 2mm thick injection-molded PVC sheets were placed in a 150℃ oven. Every 24 hours, the sheets were removed and compared with a standard color chart. The degree of yellowing was rated (1-5, with 5 indicating complete carbonization). This test simulates long-term high-temperature use and observes the color deterioration caused by thermal oxidation. Test results are shown in Table 1.

[0063] Table 1:

[0064] 2. Thermal Decomposition Temperature Test: The test was conducted using a thermogravimetric analyzer in a nitrogen atmosphere (flow rate 50 mL / min). 10 mg of PVC sample was weighed and placed in an alumina crucible. The temperature was increased from 30 °C to 600 °C at a rate of 10 °C / min. The thermogravimetric curve (TG) and differential thermogravimetric curve (DTG) were recorded. The 5% weight loss temperature (T5, characterizing initial thermal stability) and the maximum weight loss rate temperature (T0) were analyzed. max (This characterizes the intensity of thermal decomposition). The test results are shown in Table 2.

[0065] Table 2:

[0066] 3. Hydrogen chloride adsorption capacity test of hydrotalcite: The HCl adsorption capacity of modified hydrotalcite was quantified by gravimetric method. 1g of hydrotalcite sample was placed in a glass bottle with a ground glass stopper, and a dry 10% HCl-N2 mixed gas was introduced (flow rate 50mL / min). After adsorption in an oil bath at 80℃ for 2h, the surface-adsorbed HCl was removed by purging with dry nitrogen for 30min. The sample weight gain was measured using a 0.01% balance, and the adsorption capacity (mmol / g) was calculated according to the formula. The test results are shown in Table 3.

[0067] 4. Test of hydrogen chloride release per unit mass of PVC sample: 5g of PVC sample was placed in a pyrolysis apparatus and thermally decomposed at 200℃ under a nitrogen atmosphere for 1h. The generated gas was condensed in an ice-water bath and then absorbed by 50mL of deionized water. The resulting solution was titrated with 0.1mol / L NaOH standard solution using phenolphthalein as an indicator. The HCl release per unit mass of sample (mg / g) was calculated based on the volume of alkali solution consumed. The test results are shown in Table 3.

[0068] Table 3:

[0069] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A PVC additive composition based on thermal stability, characterized in that, Includes the following components in parts by weight: 30-40 parts of chlorinated polyvinyl chloride, 20-30 parts of modified hydrotalcite, 5-10 parts of calcium stearate, 3-5 parts of zinc stearate, 3-5 parts of epoxidized soybean oil, and 1-3 parts of phenolic antioxidants; The preparation method of the modified hydrotalcite includes the following steps: S1. Add magnesium nitrate and aluminum nitrate to deionized water, stir to dissolve, and obtain a metal ion solution; S2. Add polyvinylpyrrolidone to deionized water, stir to dissolve, then add polystyrene microspheres, heat and stir to disperse evenly, to obtain a polystyrene microsphere suspension; S3. Add sodium hydroxide and sodium carbonate to deionized water, stir to dissolve, and obtain a mixed alkaline solution; S4. Add the polystyrene microsphere suspension to the metal ion solution, heat and stir until uniform, then slowly add the mixed alkaline solution to adjust the pH to 9-10, heat and stir to react, so that hydrotalcite is deposited and grown on the surface of polystyrene microspheres, and perform hydrothermal aging treatment. After filtration, washing and drying, polystyrene microsphere-hydrotalcite composite is obtained. S5. The polystyrene microsphere-hydrotalcite composite was calcined in a muffle furnace to obtain porous hydrotalcite. S6. Porous hydrotalcite is modified by stearic acid intercalation to obtain modified hydrotalcite.

2. The PVC additive composition based on thermal stability according to claim 1, characterized in that, In step S4, the amount of polystyrene microspheres added is 2-5% of the total mass of magnesium nitrate and aluminum nitrate.

3. The PVC additive composition based on thermal stability according to claim 1, characterized in that, In step S4, the reaction temperature for heating and stirring is 50-60℃.

4. The PVC additive composition based on thermal stability according to claim 1, characterized in that, In step S4, the hydrothermal aging treatment temperature is 100-120℃.

5. The PVC additive composition based on thermal stability according to claim 1, characterized in that, In step S5, the calcination temperature is 300-400℃.

6. The PVC additive composition based on thermal stability according to claim 1, characterized in that, In step S6, the stearic acid intercalation modification method includes the following steps: Porous hydrotalcite is added to an ethanol solution of stearic acid, heated and stirred to react, and then filtered, washed and dried to obtain the final product.

7. The PVC additive composition based on thermal stability according to claim 6, characterized in that, The mass ratio of the porous hydrotalcite to stearic acid is 10:2-4.

8. A PVC additive composition based on thermal stability according to claim 6, characterized in that, The reaction temperature for heating and stirring in the stearic acid intercalation modification process is 80-85℃.

9. A method for preparing a PVC additive composition based on thermal stability as described in any one of claims 1-8, characterized in that, Includes the following steps: Chlorinated polyvinyl chloride, modified hydrotalcite, calcium stearate, zinc stearate, epoxidized soybean oil, and phenolic antioxidants are added to a high-speed mixer and stirred until homogeneous to obtain a mixture. The mixture is added to a twin-screw extruder and extruded and granulated to obtain a PVC additive composition.